Text Extraction from Natural Images of Different Languages Using ISEF Edge Detection - Sanjay K. Shah; Deven N. Trivedi; Keyur Chauhan; Ankur Macwan; Hitesh Chaukikar (Journal of Electronic Design Engineering, 2015)
In this paper, we proposed the algorithm text extraction of different images of languages. In computer vision research area, text is very important in images. Here, we use edge based extraction of text using ISEF (infinite symmetrical edge filter). ISEF is optimal edge detector which gives accurate results for text in images. Text extraction involves detection, localization, tracking and enhancement. Large numbers of technique have been proposed for the text extraction. Our aim is to present robust technique for text extraction of different languages images.